PEMBELAJARAN PRAKTIKUM BERORIENTASI PROYEK UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS DAN PEMAHAMAN KONSEP - Winarti, Tri; Nurhayati, Sri (Universitas Negeri Semarang, 2014)
Practicum based learning with project orientation used learning by doing principle namely process of learning outcome by doing action so could encourage students to actively study and construct their understanding. The aim of this research is to know the increasing of student’s science process skill and chemistry concept understands. Design of research is posttest only control design and samples were taken with a cluster random sampling technique, obtained the first experimental class XI IPA3, the second experimental 2 class XI IPA4. The means of test result about concept understanding of first experimental class is 85.23 and second experimental class is 78.69. The test results showed t 2.40 bigger than t 2.002 for 57 degrees of freedom and 5% significance level. It has been concluded that the average value of the postest of first experimental class is better than the second experimental class. Student’s process skill analyzed by one-way variants analysis, resulted F 10,91 bigger than F 4,01 and by scheffe methods resulted F 10,90 bigger than F critic 4,01 for practicum 1 and F 48,04 bigger than Fcritic 4,01 and by scheffe methods resulted F 48,15 bigger than F 4,01 for practicum 2. The average of student’s science process skill of first experimental class is better than the second one.Keywords: Concept Understanding, Practicum Based Learning With Project Orientation, Science Process Skills.